Towards Arginase Inhibition: Hybrid SAR Protocol for Property Mapping of Chlorinated N-arylcinnamamides - Bak, Andrzej; Kos, Jiri; Degotte, Gilles; Swietlicka, Aleksandra; Strharsky, Tomas; Pindjakova, Dominika; Gonec, Tomas; Smolinski, Adam; Francotte, Pierre; Frederich, Michel; Kozik, Violetta; Jampilek, Josef (International journal of molecular sciences, 2023)
A series of seventeen 4-chlorocinnamanilides and seventeen 3,4-dichlorocinnamanilides were characterized for their antiplasmodial activity. In vitro screening on a chloroquine-sensitive strain of Plasmodium falciparum 3D7/MRA-102 highlighted that 23 compounds possessed IC50 < 30 µM. Typically, 3,4-dichlorocinnamanilides showed a broader range of activity compared to 4-chlorocinnamanilides. (2E)-N-[3,5-bis(trifluoromethyl)phenyl]-3-(3,4-dichlorophenyl)prop-2-en-amide with IC50 = 1.6 µM was the most effective agent, while the other eight most active derivatives showed IC50 in the range from 1.8 to 4.6 µM. A good correlation between the experimental logk and the estimated clogP was recorded for the whole ensemble of the lipophilicity generators. Moreover, the SAR-mediated similarity assessment of the novel (di)chlorinated N-arylcinnamamides was conducted using the collaborative (hybrid) ligand-based and structure-related protocols. In consequence, an 'averaged' selection-driven interaction pattern was produced based in namely 'pseudo-consensus' 3D pharmacophore mapping. The molecular docking approach was engaged for the most potent antiplasmodial agents in order to gain an insight into the arginase-inhibitor binding mode. The docking study revealed that (di)chlorinated aromatic (C-phenyl) rings are oriented towards the binuclear manganese cluster in the energetically favorable poses of the chloroquine and the most potent arginase inhibitors. Additionally, the water-mediated hydrogen bonds were formed via carbonyl function present in the new N-arylcinnamamides and the fluorine substituent (alone or in trifluoromethyl group) of N-phenyl ring seems to play a key role in forming the halogen bonds.
Keywords: CoMSA; Plasmodium falciparum; arginasa; arginase inhibition; Arginase; Molecular Docking Simulation; similarity-activity landscape index; arylcinnamamides; lipophilicity; vztahy mezi strukturou a aktivitou; Antimalarials; antimalarika; Chloroquine; molecular docking; chlorochin; simulace molekulového dockingu; Structure-Activity Relationship